2015
DOI: 10.1007/s00018-015-1833-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of embryonic stem cell self-renewal: from signaling pathways to pluripotency network

Abstract: Embryonic stem cells (ESCs) can be maintained in culture indefinitely while retaining the capacity to generate any type of cell in the body, and therefore not only hold great promise for tissue repair and regeneration, but also provide a powerful tool for modeling human disease and understanding biological development. In order to fulfill the full potential of ESCs, it is critical to understand how ESC fate, whether to self-renew or to differentiate into specialized cells, is regulated. On the molecular level,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(123 citation statements)
references
References 183 publications
(215 reference statements)
1
113
0
3
Order By: Relevance
“…Network analysis of these pathways revealed a high degree of cross-talk, denoted by 112 nodes sharing 372 edges, suggesting a high degree of cooperation between mechanisms of signal transduction ( Figure 1C). Interestingly, the combined activation of Notch, WNT, and FGF signaling is implicated in the induction of pluripotent stem cells (9)(10)(11)(12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Network analysis of these pathways revealed a high degree of cross-talk, denoted by 112 nodes sharing 372 edges, suggesting a high degree of cooperation between mechanisms of signal transduction ( Figure 1C). Interestingly, the combined activation of Notch, WNT, and FGF signaling is implicated in the induction of pluripotent stem cells (9)(10)(11)(12).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1, combined database analysis of differentially expressed genes suggests enrichment of FGF (signaling by FGFR2 mutants), WNT (negative regulation of T cell factor-dependent [TFC-depen signaling is implicated in the induction of pluripotent stem cells (9)(10)(11)(12). Moreover, when expression of dysregulated genes was filtered to detect genes specifically involved in signal transduction, enrichment of genes involved in cell cycle progression and stem cell pluripotency signaling was observed (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies have demonstrated that pluripotency regulators form intricate circuits at the transcriptional level 13, 36, 53, 54, and many of the TFs ( Essrb , Klf4 , Stat3 , Tcf3 ) in these regulatory motifs are downstream effectors of the signaling pathways regulating self‐renewal and differentiation. Although the complete spectrum of signaling pathways regulating pluripotency has not been fully described 55, these results demonstrate the confluence of different environmental signals from the microenvironment for the regulation of pluripotency. It has recently been shown that within the heterogeneous population of Neural Stem Cells, there exist dormant subpopulations of cells that are able to enter a primed‐quiescent state before activation, which is accompanied by down‐regulation of glycolytic metabolism, Notch and BMP signaling, and a concomitant up‐regulation of lineage‐specific transcription factors and protein synthesis 56.…”
Section: Pluripotent State Gene Expression Heterogeneity Is Tightly Rmentioning
confidence: 81%
“…For detailed reading on mouse compared to human cell cycle regulation, refer to (Singh and Dalton 2009). For detailed reading on pluripotency network and self-renewal in human, please refer to Huang et al (2015) and Rizzino (2013).…”
Section: Regulation Of Pluripotency Self-renewal and Cell Cyclementioning
confidence: 99%